Petrographic and geochemical characteristics of late cretaceous plutonic rocks outcropping western Pertek (Tunceli): First findings - Rizeli, Mustafa Eren (My University, 2021)
This study, it was aimed to reveal the petrogenesis of the related rocks by examining the petrographic and geochemical properties of the plutonic rocks belonging to the Elazig Magmatic Complex outcropping in the Western Pertek district of Tunceli province. The geological formations in the study area are Carboniferous?Triassic Keban Metamorphics, Late Cretaceous Elazığ Magmatic Complex, Middle Eocene?Late Oligocene Kırkgeçit Formation and Late Miocene Karabakır Formation. Plutonic rocks of Elazig Magmatic Complex are in tectonic contact with Keban Metamorphics. The studied plutonic rocks are petrographically in the composition of medium-coarse grained granite, granodiorite, diorite, monzodiorite, quartz monzodiorite and quartz monzonite. These rocks generally exhibit granitic, porphyric holocrystalline, poikilitic and graphic textures. Studied rocks are ranging from tholeiitic to high-K calc-alkaline in composition and are I-type granite characters. K and Rb show positive anomalies, whereas high field strength elements such as Nb, Ta and Ti show negative anomalies in the primitive-mantle-normalised spider diagrams. These distributions in trace elements indicate that the subduction component plays a role in the petrogenesis of the related rocks. Light rare earth elements are more enriched than heavy rare earth elements in the chondrite-normalised spider diagrams. The negative Eu anomaly (Eu/Eu*=0.10?0.17) seen in the samples indicates plagioclase fractionation or retention of plagioclase in the source rock during partial melting. Particularly the high average Nb/Ta (7.28), Zr/Hf (25.11), Th/U (6.98) and Th/Ta (10.11) ratios indicate a crustal origin in the formation of these rocks. Volcanic arc granites/post-collisional field is suggested for the tectonic environment of the investigated igneous rocks.
Bildiri - Yayımlanmış
Keywords: Petrography; Geochemistry; Pertek; Tunceli; Elazığ magmatic complex